Advanced Techniques to Study Anesthetic Effects on the Nervous System - Cheng Wang (Global Journal of Anesthesiology - Peertechz Publications, 2016)
Recently, there has been increased interest and concern regarding the safety of anesthetics on the long-term impairment of the central nervous system (CNS). The field of anesthesia-related toxicology, therefore, has engaged multiple scientific disciplines in attempt to identify the basic characteristics of the anesthetic agents that produce harmful acute and/or chronic effects on the nervous system. Currently, the clinical relevance of anesthetic neurotoxicity is an urgent matter of public health.